Efecto de las diferentes fuentes de fibra en dietas de crecimiento, sobre la integridad de la mucosa intestinal de pollos de carne criados en condiciones de altura - Granda Cango, Jasmin Elisabeth (2024)
In recent years it has been observed that the inclusion of fiber can be beneficial for the development and gastrointestinal health of poultry. However, talking about fiber is very complex and depending on the nature of the fiber it can have very different effects. Therefore, in this research we sought to identify the most suitable source of fiber for the feeding of broilers raised in high altitude conditions, where the inclusion of 18% of different sources of fiber was evaluated. For this purpose, 32 Cobb 500 breed chickens were randomly distributed in 4 treatments (control, wheat bran, rice husk and palm kernel), with 8 replicates per treatment. The experimental diets were administered for 27 days, after which they were sacrificed by obtaining histological samples from the middle small intestine (jejunum) of each animal. The samples were processed and submitted to the hematoxylin and eosin staining technique, where the following variables were taken into account under a 4x objective microscope: villus length, crypt depth, ratio of villus length to crypt depth, epithelium height and muscle layer width. The diet made with wheat bran produced greater crypt depth and epithelium height (P ≤ 0.05). It was concluded that including a diet with wheat bran brings positive effects on the integrity of the intestinal mucosa in birds.